Análise do elemento transponível copia em espécies de Drosophila - Rubin, Paloma Menezes (2008)
Transposable elements (TEs) are segments of DNA that have the ability to move up and replicate themselves within the genome. The retrotransposon copia belongs to the superfamily copia and was first sequenced in D. melanogaster. We used in part of this work, which corresponded to a populational analysis of element copia in the genomes of species of the group willistoni, the portion of 5'LTR-URL for its importance as a regulatory sequence that can give us relevant phylogenetic information. Data in silico were added to the work which sought in the twelve genomes of Drosophila available the complete sequence of the element copia and the sequence of LTRs that surround the element. The wide distribution of element copia in the genus Drosophila suggests the occurrence of several cases of horizontal transfer, one of them between D. melanogaster and D. willistoni. To investigate this case we amplify by PCR the region 5'LTR-URL of two strains of D. willistoni, which showed a 95 to 98% similarity with the element copia, but the same homology was not detected in the search made by Southern blot. Some assumptions can be considered to explain these results: the copia polymorphism in the host genome, a small number of copies in a few individuals of the population or the sequence of the copia element could be in a vector. But the data are still inconclusive. The results of the searches showed a wide distribution of element copia in the genome, despite uneven, and some inconsistencies were found related to the phylogenetic analysis of the host species. Of the species examined, only three of subgenus Sophophora and two of subgenus Drosophila did not show sequences related to copia element.